Community-Embedded Hypertension Prevention: A Qualitative Study of Promotive and Preventive Strategies in Urban Indonesia - Apir; Widyowati, Agustin; Nurwijayanti (KHD Production, 2026)
Hypertension remains a critical non-communicable disease requiring comprehensive control strategies beyond purely curative clinical interventions. This study explores promotive and preventive health strategies used to mitigate the rising incidence of hypertension in the Palangka Raya City community. Employing a qualitative phenomenological design, researchers captured the lived experiences and strategic implementations of frontline health practitioners. Data collection encompassed in-depth interviews, direct observations, and comprehensive document reviews, utilizing rigorous source and method triangulation to ensure analytical credibility. The diverse participant cohort included public health workers, non-communicable disease program coordinators, community health cadres, hypertension patients, and Community Health Center directors. Ethical approval was obtained prior to data collection. Thematic analysis guided the systematic data reduction, presentation, and conclusion phases. Findings reveal that effective hypertension control relies on four interconnected operational pillars: data-driven advocacy, robust social support, grassroots community empowerment, and integrated promotive-preventive health services. These operational strategies strongly align with the Ottawa Charter principles and Social Support Theory, demonstrating how familial and communal networks facilitate sustained behavioral modifications. The research ultimately concludes that successful hypertension mitigation necessitates synergistic cross-sectoral collaboration, continuous social reinforcement, and sustainable community engagement. Integrating promotive and preventive paradigms through targeted health promotion offers a highly effective, scalable framework for reducing cardiovascular risks and improving long-term population health outcomes across diverse resource-constrained urban settings globally.